Odontogenic Differentiation Induced by TGF-β1 Binding Peptide–Modified Bioglass. (September 2022) - Wu, J.; Mao, S.; Xu, L.; Qiu, D.; Wang, S.; Dong, Y.
Emerging evidence suggests that growth factors are crucial in regenerative endodontic therapy. To achieve the desired effects, the systematic administration of supraphysiologic concentrations of exogenous growth factors is commonly performed, but this is usually associated with high costs, technique, and safety issues. Here, we describe a novel biomaterial that can manipulate endogenous growth factors without the need for adding exogenous growth factors. Transforming growth factor β1 binding peptide (TGFp) was grafted onto the surface of a neutral pH phytic acid–derived bioactive glass (PSC) to synthesize modified bioactive glass (PSC-TGFp). Fourier transform infrared spectroscopy and thermogravimetric analysis results demonstrated that the TGFp was successfully grafted to the surface of the PSC. Scanning electron microscopy and x-ray diffraction showed that PSC-TGFp possessed good in vitro bioactivity. After soaking in simulated body fluid for 24 h, hydroxyapatite formed on the surface of PSC-TGFp. Enzyme-linked immunosorbent assay showed that PSC-TGFp could capture endogenous transforming growth factor β1 from dentin matrix–extracted proteins (DMEP) and release it slowly over 21 d. Cytologic experiments revealed that PSC-TGFp after adsorbing DMEP could enhance the adhesion, migration, viability, and odontogenic differentiation of stem cells from apical papilla. The results highlight that PSC-TGFp may be a promising biomaterial to manipulate endogenous growth factors for regenerative endodontic therapy in the future.